Predictors of fatigue in sarcoidosis: The value of exercise testing. (July 2016) - Strookappe, Bert; De Vries, Jolanda; Elfferich, Marjon; Kuijpers, Petra; Knevel, Ton; Drent, Marjolein
Abstract: Background: Sarcoidosis patients often are troubled by dyspnea, exercise limitation, and fatigue. Many patients (up to 50–81%) suffer from sarcoidosis-associated fatigue. The etiology of fatigue in sarcoidosis is still unclear. Objective: The aim of this study was to assess the relationship between fatigue and both exercise capacity and clinical characteristics in sarcoidosis patients. Additionally, we studied the predictive value of exercise test results and other relevant clinical characteristics for the independent variable of fatigue. Methods: From November 2012 to September 2014, 201 sarcoidosis outpatients were referred to the Dutch ILD care foundation expertise team, 146 of whom were included in this retrospective cohort study. All patients completed the Fatigue Assessment Scale (FAS). Exercise capacity was assessed by the 6-min walking distance (6MWD) and steep ramp test (SRT) result. Clinical data were gathered from the medical records. Results: Exercise capacity only showed a weak correlation with fatigue ( r = 0.25, p = 0.002 for 6MWD % of predicted; r = 0.24, p = 0.003 for SRT). Fatigue was not correlated with the demographic variables of age, body mass index, or time since diagnosis. Inflammatory markers, lung function tests, and hand grip strength showed no significant correlations with fatigue. Backward multiple regression analysis showed that only female sex (t = −2, 614, p = 0.01) and 6MWD % of predicted (t = −2.773, p = 0.006) were independent predictors of fatigue. However, the r 2 indicated that these two variables together explained only 11% of the FAS score. Conclusions: These results show that exercise capacity partly predicts patients' fatigue scores. Fatigue was not explained by lung function test results, inflammatory markers, or other clinical parameters. Highlights: Fatigue is a substantial multifactorial problem among sarcoidosis patients. Sarcoidosis-related fatigue is not explained by lung function tests. Sarcoidosis-related fatigue is only partially predicted by exercise capacity. The Steep Ramp Test can be a useful alternative maximal effort test.